PENINGKATAN HASIL BELAJAR MAHASISWA MELALUI PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) PADA MATA KULIAH MATEMATIKA EKONOMI - Henny Indrawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
This study aims to improve student learning outcomes through the application of TGT learning models in Mathematical Economics course. The experiment was conducted at Economic Education Program, the Faculty of Teachers’Training of Education, Riau University. Subjects were students of the second semester of Economic Education Program attending in Mathematical Economics in Academic Semester 2011/2012, totaling 36 students, consisting of 28 (78 percent) female students and 8 male students (22 percent). The research was conducted in three cycles, each cycle includes the planning, implementation, observation and reflection. The results found that the implementation of TGT learning in Mathematical Economics can improve student learning outcomes. Using TGT as a learning model for improving student learning outcomes will be effective if supported by the following: the ability of lectures to create lesson plans based on the TGT model, and the involvement of students in proportion to the activity in the learning process. Keywords: Teams Games Tournament (TGT), Mathematical Economics, Learning Outcomes